Checklist of the flower flies of Ecuador (Diptera, Syrphidae) - Diego Marín-Armijos; Noelia Quezada-Ríos; Carolina Soto-Armijos; Ximo Mengual (ZooKeys, 2017)
Syrphidae is one of the most speciose families of true flies, with more than 6,100 described species and worldwide distribution. They are important for humans acting as crucial pollinators, biological control agents, decomposers, and bioindicators. One third of its diversity is found in the Neotropical Region, but the taxonomic knowledge for this region is incomplete. Thus, taxonomic revisions and species checklists of Syrphidae in the Neotropics are the highest priority for biodiversity studies. Therefore, we present the first checklist of Syrphidae for Ecuador based on literature records, and provide as well the original reference for the first time species citations for the country. A total of 201 species were recorded for Ecuador, with more than 600 records from 24 provinces and 237 localities. Tungurahua, Pastaza, and Galápagos were the best sampled provinces. Although the reported Ecuadorian syrphid fauna only comprises 11.2 % of the described Neotropical species, Ecuador has the third highest flower fly diversity density after Costa Rica and Suriname. These data indicate the high species diversity for this country in such small geographic area.